The jeong and haan of Vincent van Gogh: neuropeptides of bondedness and loss - Lee, Sung W.; Cullen, Kathryn R.; Rim, Sung-ryun; Toddes, Carlee (Frontiers in Psychology, 2024)
We introduce two Korean-named yet transcultural feelings, jeong and haan, to fill gaps in neuroscientific understanding of mammalian bondedness, loss, and aggression. Jeong is a visceral sense of connectedness to a person, place, or thing that may arise after proximity, yet does not require intimacy. The brain opioid theory of social attachment (BOTSA) supports the idea that jeong involves increased activity of enkephalins and beta-endorphins. We propose that withdrawal of jeong-related neuropeptides leads to original haan, a sense of "missingness" that is too subtle to be grossly dysphoric. Through narrative, cognitive appraisals, or moral assignments, however, original haan may transform into the feeling of constructed haan -resentment, bitterness, grievance, sorrow, or suppressed anger. In males, the transformation may be driven by arginine vasopressin, an ancient fight-or-flight neurohormone. Constructed haan may also be driven by vasopressin in females, though data is more sparse, and in both sexes it may depend on situational or societal context. Endogenous opioids inhibit vasopressin, so that when jeong diminishes, vasopressin release may become disinhibited. This relationship implies a companion to the BOTSA, which we articulate as the brain opioid and vasopressin theory of original and constructed haan (BOVTOCH). To illustrate, we reflect on borderline personality disorder, and Vincent van Gogh's self-severing of his ear while living and working with Paul Gauguin, and fearing abandonment by him; yet to understand Van Gogh more completely we also present the brain opioid theory of stable euphoric creativity (BOTSEC), to model the subjective "highs" associated with creative flow states. Together these brain opioid theories may help to explain how feelings related to social bondedness can influence a range of phenomena. For example, opioid drug dependence may be, at least partly, a maladaptive response to feelings of isolation or disconnectedness; the health protective effects of social bonds could be related to tonic exposure to endogenous opioids and their anti-inflammatory properties; endogenous opioid-based social relational enhancement may contribute to placebo responding. Finally we conclude by pointing out the possibility of virtuous cycles of social connectedness and creativity, when feelings of bondedness and euphoric flow reinforce one another through endogenous opioid elevation.